Treatment of natural rubber wastewater using oil palm empty fruit bunch, kaolin and zeolite as composite adsorbent - Nasir, Nazlizan (2018)
The development of composite adsorbents is a new technique applied in wastewater treatment. A combination of few absorbents is proven to be capable of removing pollutants simultaneously compared to a single adsorbent. Thus, the aim of this study is to produce a composite adsorbent from natural zeolite, oil palm empty fruit bunch (EFB) and kaolin bound to chitosan to adsorb colour, chemical oxygen demand (COD) and ammoniacal nitrogen (NH3-N) from natural rubber wastewater. Batch and fixedbed adsorption techniques were used in this study. The combination ratio of zeolite, EFB and kaolin as a composite was optimised using D-optimal mixture design (DMD) while the characterization of composite adsorbents was done using Fourier Transform Infrared (FTIR), Field Emission Scanning Electron Microscopy (FESEM), Brunauer- Emmett-Teller (BET) and zeta potential. Batch experiments were carried out to determine the influence of various factors namely adsorbent dosage, pH, shaking speed and contact time of adsorption colour, COD and NH3-N on the composite adsorbent. Langmuir and Freundlich models were used to investigate isotherm adsorption while pseudo-first order, pseudo-second order, intra-particle diffusion and Elovich were used to examine kinetic behaviour. The fixed-bed adsorption performances were evaluated by varying the influent flow rate (2, 2.5 and 3 mL/min) while the adsorption kinetics was analysed using Thomas, Yoon-Nelson and Adam-Bohart kinetic models. The regeneration of the composite adsorbent for up to five adsorption/desorption cycles was also investigated. According to the results, the composition of 0.4g zeolite, 0.8g EFB and 0.8g kaolin was the best ratio in terms of colour, COD and NH3-N removal from natural rubber wastewater. FTIR and FESEM analyses before and after adsorption revealed that ion exchange was the main mechanism involved. The BET surface area of the composite adsorbent was 55.30 m2/g. Meanwhile, negative values of zeta potential showed promising results for the adsorption process. The best conditions for the effective adsorption of colour, COD and NH3-N from natural rubber wastewater onto composite adsorbents were found to be 3g of adsorbent pH 7, 150 rpm shaking speed and 100 min contact time. The maximum removal of color, COD and NH3-N using composite adsorbents from natural rubber wastewater was 98%, 87.2% and 94.2% respectively. The investigation of adsorption isotherms model showed that the adsorption isotherm data fitted well to the Langmuir isotherm. This indicated that the monolayer coverage on the composite adsorbent was dominant. On the other hand, the adsorption kinetics complied well with the pseudo-second-order kinetic model which indicated that the rate of the sorption reaction was controlled by the second-order mechanism (chemisorption). Column adsorption demonstrated that the removal of colour, COD and NH3-N can reach up to 99.99% at a lower flow rate of 2 ml/min which results in a longer breakthrough and exhaustion time. Meanwhile, the experiment data was found to comply well with the Thomas and Yoon-Nelson model rather compared to the Adam-Bohart model. The regeneration study achieved three (3) adsorption cycles of the spent composite adsorbent. In conclusion, the present study was able to prove that composite adsorbent is a promising adsorbent for the removal of colour, COD and NH3-N from natural rubber wastewater.